Improving the recording of surgical drain output. Issue 1 (4th September 2015) - Lyons, Nicholas; Heron, Paul; Bethune, Rob
Abstract: Monitoring the output from surgical drains is an important part of post-operative care and is often undertaken poorly. Failure to have accurate documentation of daily outputs may delay the removal of drains and increase the risk of complications. Following discussions with medical and nursing staff we listed eight key criteria that should be routinely monitored for surgical drains. A baseline measurement demonstrated only 20% compliance with these criteria. As such we decided to design a chart, after discussing with the multidisciplinary team, with adequate space to document drain output clearly. Post-intervention data collection showed a reasonable uptake of the chart (70%) with overall criteria compliance increasing to 55%. We made further interventions designed to raise awareness of the chart, which increased chart uptake to 79% and compliance to 63%, leading to the adoption of the chart by the department. Twelve months after introducing the chart we conducted a final data collection which demonstrated the chart was now being used in 100% of patients and that overall criteria compliance had increased to 78%. While some of the key criteria are still not documented for all patients, we have demonstrated that the introduction of a simple and well-designed drain chart can significantly improve the documentation of drain output, thereby improving patient safety and discharge efficiency.